A review of surgical techniques of lumbar disc herniation - Gołębiowska, Natalia (Medical Studies/Studia Medyczne, 2018)
Lumbar disc herniation is caused by degenerative changes in the intervertebral disc, and is one of the most common causes of disability for people under 45 years old. The most commonly affected regions are the L4/L5 and L5/S1 levels. When conservative treatment does not bring the expected result, surgical treatment is necessary. Fast recovery, early mobilisation, and short hospitalisation is what patients expect nowadays. There are a wide range of surgical techniques available, from open surgeries, such as laminectomy, hemilaminectomy, and microdiscectomy, to minimally invasive surgeries, such as percutaneous endoscopic lumbar discectomy, which are becoming more and more popular. Microdiscectomy is a gold standard in spine surgery for lumbar disc herniation.